2015
DOI: 10.1093/jme/tju019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Insect Growth Regulators Against Field-Collected Aedes aegypti and Aedes albopictus (Diptera: Culicidae) from Malaysia

Abstract: Susceptibility status of Aedes aegypti (L.) and Aedes albopictus Skuse larvae obtained from 12 states in Malaysia were evaluated against five insect growth regulators (IGRs), namely, pyriproxyfen, methoprene, diflubenzuron, cyromazine, and novaluron under laboratory conditions. Field populations of Ae. aegypti exhibited moderate resistance toward methoprene and low resistance toward pyriproxyfen, with resistance ratios of 12.7 and 1.4, respectively, but susceptibility to diflubenzuron, cyromazine, and novaluro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 18 publications
1
44
0
1
Order By: Relevance
“…aegypti and Ae . albopictus populations from 12 states in Malaysia displayed variable levels of resistance to 5 IGRs [75]. …”
Section: Resultsmentioning
confidence: 99%
“…aegypti and Ae . albopictus populations from 12 states in Malaysia displayed variable levels of resistance to 5 IGRs [75]. …”
Section: Resultsmentioning
confidence: 99%
“…aegypti exhibited moderate resistance toward Methoprene and low resistance toward Pyriproxyfen, with resistance ratios of 12.7 and 1.4, respectively, but susceptibility to Diflubenzuron. 24 In this study, comparing the larvicidal activity of Methoprene with Diflubenzuron and Temephos (Table 1 and 2) it can be inferred that Methoprene is more effective against Ae. aegypti and can be used as an alternative larvicide in the areas where the low efficacy of Diflubenzuron and high resistance to organophosphate compounds have been detected.…”
Section: Larval Susceptibilitymentioning
confidence: 68%
“…21 In Malaysia, Aedes larvae tolerance against temephos has been reported and have exhibited moderate resistance toward methoprene and low resistance toward pyriproxyfen 22,23 , but susceptible to diflubenzuron, cyromazine, and novaluron. 24 During the past two decades, considerable progress has been made in the development of natural and synthetic compounds known as insect growth regulators (IGRs) which are capable of interfering with the process of growth, development, and metamorphosis of the target mosquito species. Two types of IGRs are available, one which inhibit the growth of larvae (Methoprene and Pyriproxyfen) due to juvenile hormone-like action and known as JH mimics or analogs and the other type of IGR compound (Diflubenzuron) which interferes with chitin production leading to moulting disturbances, resulting in the death of the insect.…”
mentioning
confidence: 99%
“…There are number of IGRs such as, diflubenzuron, endotoxins, and methoprene that have been used to counter viral infections spread by A. aegypti (Abbas et al, 2014). According to Lau et al, field population of vector species develops resistance to certain IGRs; and in their study, they found that cyromazine showed effective results in attenuating larval population indices of A. aegypti (Lau et al, 2015). …”
Section: Introductionmentioning
confidence: 99%